Experimental study of thermal runaway process of 256Ah prismatic nickel-rich battery - Wei, Ningning; Li, Minghai (Frontiers in Energy Research, 2023)
Lithium-ion batteries (LIBs) are plagued by risks of combustion and explosion during thermal runaway (TR), which hinder their broader applications. Currently, there is limited research on thermal runaway experiments for batteries with a capacity exceeding 200 Ah. In this study, a non-commercial 256 Ah prismatic battery was utilized, featuring Li (Ni0.8Mn0.1Co0.1)O2 as the cathode material and silicon-doped graphite as the anode material. The investigation focused on the thermal runaway characteristics of the battery under 100% state of charge (SOC) conditions. Three repetitive thermal runaway experiments were conducted within a 1000L lithium battery constant volume test chamber (AEC) under a nitrogen environment. Temperatures at various points within the battery were recorded during the experiments, and high-speed cameras were employed to capture moments of thermal runaway. The research findings are as follows: 1) The ejection velocity of smoke at the instant of safety valve opening was measured at approximately 140 m/s, while the velocity of the ejected flame was approximately 55 m/s. 2) Within an extremely short time range after safety valve opening, the temperature at the safety valve nozzle reached a peak value of 701.8°C ± 42 C. 3) The average duration of ultra-high-speed ejections was measured at 5.0 ± 1.6 s, high-speed ejections lasted for 11.9 ± 2.7 s, and slow-speed ejections exhibited an average duration of 21.6 ± 3.7 s, resulting in a total ejection duration of 36.2 ± 4.7 s. This study provides valuable insights into the original state of the jetting process during thermal runaway in high-capacity LIBs and offers certain guidance for BTMS design.